Reservoir bank slope in laxiwa hydropower station, china - Zhang, Dexuan; Wang, Gonghui (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="[null,2,"Laxiwa Hydropower Station is situated on the main reach of the Yellow River, China. The construction was started in October 2001, and impoundment started in March 2009. However, from May 2009, the right-bank slope of the reservoir, about 700 m high and 1000 m wide about 500m far from the dam, was found to be deforming greatly and continuously. Although this slope had been identified as an old landslide, the survey before the construction of the dam concluded that this slope is stable and will be stable even after the impoundment. Thus, the slope was not monitored before the visible deformation occurred after the impoundment. To identify the relationship between the slope deformation and impoundment, we utilized D-InSAR and ALOS Prism data to analyze the slope deformation before and after impoundment. We found that there was no identifiable deformation before the impoundment, and the maximum horizontal displacement reached approximately 7.5m during the period of 3 April 2009 to 22 May 2010 after impoundment. Although the potential sliding surface has not been identified irrespective of the performance of a lot of survey works, we concluded that the instability of this high and steep slope will be great threaten to the dam as well as to the downstream residents."]" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Laxiwa Hydropower Station is situated on the main reach of the Yellow River, China. The construction was started in October 2001, and impoundment started in March 2009. However, from May 2009, the right-bank slope of the reservoir, about 700 m high and 1000 m wide about 500m far from the dam, was found to be deforming greatly and continuously. Although this slope had been identified as an old landslide, the survey before the construction of the dam concluded that this slope is stable and will be stable even after the impoundment. Thus, the slope was not monitored before the visible deformation occurred after the impoundment. To identify the relationship between the slope deformation and impoundment, we utilized D-InSAR and ALOS Prism data to analyze the slope deformation before and after impoundment. We found that there was no identifiable deformation before the impoundment, and the maximum horizontal displacement reached approximately 7.5m during the period of 3 April 2009 to 22 May 2010 after impoundment. Although the potential sliding surface has not been identified irrespective of the performance of a lot of survey works, we concluded that the instability of this high and steep slope will be great threaten to the dam as well as to the downstream residents.